A FLEXIBLE MANUFACTURING SYSTEM RESCHEDULING MODEL CONSIDERING CUTTING TOOLS CONDITIONS - SETIAWAN (NIM : 33412001), ARI
Flexible Manufacturing System (FMS) is an automated production system consisting of CNC machines integrated with a material handling system and controlled by a computer. The FMS is suitable to process in medium quantities of products variations and medium number of the production volumes. The FMS configuration in this study consists of several similar CNC machines equipped with the same type and number of cutting tools in each tool magazine. The CNC machines are equipped with one buffer to store the material waiting to be processed. The FMS has the material handling system consists of a stacker crane and a pallet stocker. The main characteristics of the FMS are automatic and flexible. The automatic characteristic indicates the ability to operate without having to be controlled by the operator (unmanned), whereas one of the FMS flexibility is routing flexibility which is the ability to provide an alternative route when there is interference. Scheduling on FMS is the process of allocating and sorting the work on the machines. Rescheduling is required when a disturbance is occurred. The disturbance could come from job related or resource (FMS equipment) related. Based on literature review, it is found the rescheduling model caused by only the machine failure. Meanwhile the rescheduling model caused by the cutting tools failure has not been developed. Thus the research question in this dissertation is how the formulation of the production rescheduling model on the FMS caused by the event of cutting tool disruption. The purpose of this study is to obtain a rescheduling model of FMS concerning the cutting tool life time. The proposed model has the ability to select CNC machines and cutting tools simultaneously. The research methodology starts from literature review and observations on the real system to obtain the problem formulation, and then determines the configuration and the FMS operating system. The next stage is the development of the scheduling model consisting of four models. The Model-1 is the static scheduling for the jobs on machines and cutting tools simultaneously. The Model-1 creates the initial schedule. At the time when the FMS operates, there is an event of broken cutting tool, for which a rescheduling model is required. The purpose of the rescheduling Model-2 is to obtain the new schedule using the mechanisms used in the Model-1. The characteristics of the rescheduling Model-2 resulted in the new schedule that the job allocation on the machine was different from the initial schedule. To maintain the job allocation on the machine, the rescheduling Model-3 was developed, assuming the availability of the spare cutting tools. The rescheduling Model-4 is the final model which is the result of this study. The rescheduling process in the Model-4 concerns the location of the material on the FMS. If the material is already prepared in the CNC-machine buffer, then the job will be maintained by the Model-3. Meanwhile, if the material is waiting in pallet stocker, then the job will be rescheduled by Model-2. In Model-1, a series of trials has been conducted to obtain an initial schedule. Using analytic approach by Lingo, global optimal solution is found for small FMS configuration that consists of two machines, two types of cutting tools, two units of each cutting tools, two jobs with two stages each, and two operations on each stage. For a bigger problem, such as four jobs with two stages each and two operations on each stage, global optimal solution cannot be found. In the rescheduling Model-2 and the rescheduling Model-3, a series of trial has been carried out with analytic approach and obtain the optimal results. The results in Model-2 show that the work allocations on the machines are different with the initial schedule. Model-3 provides a new schedule that maintains the allocation of work on the machine in accordance with the initial schedule, so long as there is the spare cutting tool. In Model-4, data processing is needed from the initial schedule to determine the location of the material and the availability of spare cutting tools. If the materials are already on the machine buffers, the jobs will be rescheduled with the Model-3 approach. Meanwhile, if the materials are still in the pallet stocker, then the jobs will be rescheduled by the Model-2 approach. Many variables and parameters are involved. Therefore the solution searching in Model-4 has to be done by heuristic approach. The object oriented modeling (OOM) is proposed to be the solution searching method in the Model-4 problems. The principle of the OOM is to create the model of FMS elements into objects that can interact with each other. The objects are classified into four classes, which are the product-class, the CNC-machine-class, the cutting-tool class and the pallet-stocker-class. Every object has the attributes and the method. The attributes will characterize the object, while the method is the algorithm that has the ability to interact between objects. The Model-4 with the OOM approach has been built into an application based on java language software. In this application, a series of trials for complex FMS problems has been conducted. The FMS consists of four machines, 12 types of cutting tools, each of three units for 15 jobs, each consisting of five to seven operations. The trials show that the Model-4 has flexible characteristics to provide the new schedules as the quick respond (in one second) of the cutting tool failure event.